Características estereotípicas que intervienen en el proceso de evaluación de candidatos electorales - Papuico Navarro, Korina Eiko (2014)
The data indicates that in low information context, some characteristics of the candidates may be key for voters, who tend to observe it and take shortcuts when deciding, engaging social categorization processes. From the description of three easily detectable features –sex, age and racial group- and a political feature -subject matter policy of public involvement- participants were asked to attempt to assess who is the most likely to win elections. It is used a new analysis tool in Psychology that shows predictive validity in market research and proven reliability: Conjoint analysis. The main findings of the relative importance given to each candidate features are discussed depending on the segment in which it was possible to divide the sample –by sex and socio-ethnic group.